Advances in neurophilosophy - Heinzelmann, Nora (Bloomsbury Publishing Plc, 2024)
Intro -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Figures -- Contributors -- Introduction to neurophilosophy: Nora Heinzelmann -- Chapter 1: How the perception of vocal emotions can be measured through intracranial recordings in the human brain -- Chapter 2: Electrophysiology, human agency and moral psychology -- Chapter 3: Finding feelings of responsibility in the human brain with magnetoencephalography -- Chapter 4: From 'blobs' to mental states: The epistemic successes and limitations of functional magnetic resonance imaging -- Chapter 5: Resting-state fMRI and cognitive neuroscience -- Chapter 6: Using TMS to test hypotheses about the causal roles of specific brain regions -- Chapter 7: Transcranial direct-current stimulation -- Chapter 8: Cognitive computational neuroscience -- Chapter 9: Individual development: Developmental neuroscience -- Chapter 10: About leaving the neuroscience laboratory -- Index.
Description based on publisher supplied metadata and other sources